2005
DOI: 10.1007/s10772-006-6368-3
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia Quality as a Function of Bandwidth, Packet Loss, and Latency

Abstract: Two experiments examined the judged quality of videoconferencing as a function of three measures of IP network performance: bandwidth, latency, and packet loss. The experiments were realized in a laboratory using a network emulator and a commercial videoconferencing system. Experiment 1 used a fractional factorial design and all three parameters:• Bandwidth: 128 kbits/s, 384 kbits/s, 768 kbits/s • Latency: 0, 150, 300 ms one-way • Bursty packet loss: 0, 2%, 4% (using the "Gilbert-Eliot" method).Experiment 2 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It has been discovered that jitter may degrade the quality of video by the same amount that packet loss does, and that even a low-level impairment of jitter or packet loss can alter the way video is perceived to be of lesser quality [10]. Studies have been done on the effects of packet loss and latency, and the findings have shown that packet loss is a more relevant factor than delay in determining perceived quality [11]. The effect of latency and jitter on the quality of experience of playing the Call of Duty: Modern Warfare 2 game is shown, and it was discovered that jitter has a significant influence on the quality that is perceived [12].…”
Section: Related Workmentioning
confidence: 99%
“…It has been discovered that jitter may degrade the quality of video by the same amount that packet loss does, and that even a low-level impairment of jitter or packet loss can alter the way video is perceived to be of lesser quality [10]. Studies have been done on the effects of packet loss and latency, and the findings have shown that packet loss is a more relevant factor than delay in determining perceived quality [11]. The effect of latency and jitter on the quality of experience of playing the Call of Duty: Modern Warfare 2 game is shown, and it was discovered that jitter has a significant influence on the quality that is perceived [12].…”
Section: Related Workmentioning
confidence: 99%
“…Using packet loss bursts of different length Liang et al demonstrated that the memory of the packet loss process significantly affects MSE measure of the picture quality [61]. Using Gilbert-Elliot model of packet losses with different autocorrelation properties it has been shown that the perceived video quality may significantly vary for the same packet loss ratio [30]. Using different objective and subjective performance metrics importance of the autocorrelation in the packet loss process have been reported in other studies as well (see e.g.…”
Section: Network-related Metricsmentioning
confidence: 99%
“…To compensate for this lack of direct vision of the environment, cameras and video transmission equipment are often installed in the operation area. However, the data network and video stream encoding and decoding introduce a delay, or latency, between what the operator sees, and what is actually happening, which adds difficulties to teleoperation [1,2]. Due to the mentioned latency, the poor visibility of the environment, and the used 2D visualization interfaces, hammer tele-operation requires highly skilled operators that are trained to deal with these two phenomena.…”
Section: Introductionmentioning
confidence: 99%